First isolation, in-vivo and genomic characterization of zoonotic variegated squirrel Bornavirus 1 (VSBV-1) isolates - Kore Schlottau; Daniel Nobach; Christiane Herden; Stefan Finke; Martin Beer; Donata Hoffmann (Emerging Microbes and Infections)
The variegated squirrel bornavirus 1 (VSBV-1), a member of the family Bornaviridae, was discovered in 2015 in a series of lethal human infections. Screening approaches revealed kept exotic squirrels as the putative source of infection.Infectious virus was successfully isolated by co-cultivation of infected primary squirrel cells with permanent cell lines. For in vivo characterization, neonatal and adult Lewis rats were inoculated either intracranially, intranasally or subcutaneously. After 4.5 months, three out of fifteen neonatal intracranially inoculated rats were VSBV-1 genome positive in the central nervous system without showing clinical signs. Pathohistological examination revealed a non-purulent encephalitis. While infection of immune incompetent rats (neonatal) using the type species of mammalian bornaviruses, the Borna disease virus 1, proceed to an immune tolerant status, VSBV-1 infection could result in inflammation of neuronal tissue. Sequencing showed minor adaptations within the VSBV-1 genome comparing to the viral genomes from infected squirrels, cell cultures or rat tissues.In conclusion, we were able to generate the first VSBV-1 isolates and provide in vivo animal model data in Lewis rats revealing substantial differences between VSBV-1 and BoDV-1. Furthermore, the presented data are a precondition for insights into the transmission and pathogenesis of this novel zoonotic pathogen.